SYNTHESIS OF MODEL THE LUENBERGER OBSERVER FOR EXTERNAL CYLINDRICAL GRINDING PROCESS - Sergey BRATAN; Denis SIDOROV; Yury GUTSALENKO (Fiabilitate şi Durabilitate)
The problem of diagnosing the actual depth of cut at cylindrical grinding is considered.A mathematical model of the behavior of the grinding wheel and the workpiece during processingis worked out. According to this model it is produced a synthesis the model of the Luenbergerobserver with the Kalman filter to control the process of external cylindrical grinding. Thedeveloped approach is to improve the accuracy of control and the related with them computationalprocedures of assessment and management